Use of ICT in indigenous primary school classroom: A case study of teachers' expectations and experiences - Aziz N.; Rahman N.A. (IEEE Computer Society, 2023)
Education; Information systems; Metadata; Cultural backgrounds; ICT infrastructures; ICT Teacher; Indigenous; Information and Communication Technologies; Primary schools; Real situation; Teaching and learning; Teaching